Quantity determination of Recorcinol compound by the Reaction with Ferric nitrate dissolved in nitric acid (Journal of the College of Basic Education, 2023)
By this paper we development of an analytical method to determine Recorcinol compound by coupling reaction for diazotized solution of Ferric nitrate dissolved in nitric acid in the presence of buffer solution Na2HPO4 (PH= 10.8) to give a compound with a single azo dye salt having orange color soluble in water with high absortivity at a wave length 449 nm , an early study to have a perfect optimum condition was made for the determination. A calibration curve for a range of concentration (5-75)pm was taken and the value of molar absortivity was 1.5*103 L.mol-1.cm-1 with a relative standard divation more than 1.26% and a recovery 98.77% .Also as we study the nature of the azo dye by mole fraction method, from the practical value we found that the mole fraction of the dye compound is 1:1(Recorcinol: Ferric nitrate dissolved in nitric acid) and the stability factor reach to 1.4*106 L.mol-1 .